Redesigning a hydraulic subsystem for a Volvo hauler, focusing on cost efficiency - Andersson, Magnus; Oldberg, Einar (My University)
The modern day hauler is a piece of heavy machinery used in moving large payloads within and between worksites. As the payload of the vehicle increases, so does the need for a robust and reliable hydraulic brake system, ensuring the safety of both the drivers and their surroundings. One of the companies working on producing and improving these machines are Volvo Construction Equipment [VCE] , who since 1966 have been in the forefront of engineering in this field. The aim of this thesis is to conduct a concept study for VCE regarding an upcoming design for a hydraulic system and to provide alternatives to reduce the overall price of the system, as well as the quality in regards to performance and leaks. The current design, serving as a reference to the project, includes a lot of complexities and has issues pertaining to the mounting of the system and the cost of production. This is due to several factors, including the narrow areas between components, overlapping parts, as well as the complexities of several valves and blocks. As the current design of the system is known, a reference for the layout and function is included, as well as an understanding of which functions are essential. Using the standards of product development and testing the systems layout and performance, this study explores a few different alternatives to the current concept by VCE and provides recommendations from the group, as well as aspects of the design that can be developed further by the engineers at Volvo. The proposed solutions have been put through a process of matrices and designed in the design program CATIA V5 . In the end of the project a few results were concluded. Firstly a digital construction of the hydraulic system with modifications to the hydraulic distribution, layout and newly constructed blocks. This system is meant to serve as an inspiration for VCE to further develop their system in the future. Secondly two smaller concept studies were evaluated, where an attempt of moving a key component was made, as well as a concept replacing the hydraulic hoses with metal tubing. These concepts were deemed unfit for further development, serving as a concept study as recommendations to not develop further. Lastly a looser concept study was conducted to recommend the further development of an idea of merging several of the components in the design. This was never modeled, but serves as a recommendation to VCE for future research. Based on this investigation there are still factors that can be evaluated for further improvements. Thus, the results and discussion of this thesis may serve as a basis for what concepts that are and aren’t relevant for future research.